Volume 8: Turbomachinery, Parts A, B, and C 2012
DOI: 10.1115/gt2012-68288
|View full text |Cite
|
Sign up to set email alerts
|

Cavity Flow Modeling in an Industrial Centrifugal Compressor Stage at Design and Off-Design Conditions

Abstract: Numerical tools and test equipments used in the design and validation of modern centrifugal compressor stages need to be at the state-of-the-art. In particular, a big effort is currently made to correctly model secondary flows that play a relevant role in the accuracy of the performance prediction. This paper presents the flow analysis of a high efficiency centrifugal compressor stage using high accurate computational fluid dynamics with a particular attention to the cavity flows modeling. Experimental data we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The suction mode was beneficial to the mainstream flow, while the injection mode was harmful. Guidotti et al 20 numerically and experimentally investigated the effects of the cavity flow on the compressor performance. It was found that the three-dimensional numerical simulation including full cavity structure was excellent in predicting the overall performance and flow features details for the compressor.…”
Section: Introductionmentioning
confidence: 99%
“…The suction mode was beneficial to the mainstream flow, while the injection mode was harmful. Guidotti et al 20 numerically and experimentally investigated the effects of the cavity flow on the compressor performance. It was found that the three-dimensional numerical simulation including full cavity structure was excellent in predicting the overall performance and flow features details for the compressor.…”
Section: Introductionmentioning
confidence: 99%
“…Literature shows that the inclusion of rotor-stator cavities is crucial to the correct reproduction of stage characteristics: (Hu et al, 2017) and (Sun et al, 2009), amongst others, research centripetal flow through rotor-stator cavities and show how axial thrust and disk torque are affected. (Guidotti et al, 2012) show the influence of cavity modelling on the efficiency and pressure ratio. (Mischo et al, 2009) find that the shroud cavity leakage can induce flow separation and thereby severely influence compressor performance.…”
Section: Introductionmentioning
confidence: 99%